Pengaruh Gaya Kepemimpinan Kepala Desa Terhadap Loyalitas Perangkat Desa Tobungin di Kabupaten Banggai Kepulauan: The Influence of the Village Head's Leadership Style on the Loyalty of the Tobungin Village Officials in the Banggai Islands Regency - Muhamad Alfarisi Aher; Sri Mulyaningsih Kamaru (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2023)
This study aims to find out how the influence of the Village Head's Leadership Style on the Loyalty of Tobungin Village Officials, Tinangkung Selatan District, Banggai Kepulauan Regency. The research approach used is a quantitative qualitative approach. The sample in this study amounted to 16 people. The type of data in this study is primary data. The data collection technique was carried out by distributing questionnaires to all Tobungin Village Officials. The data analysis technique used is simple linear regression analysis, namely Y = 10,293 + 0,593 X, this shows a positive and unidirectional relationship. Calculation of the correlation coefficient of 0.510 this value shows the closeness relationship between the independent variables, namely the Village Head's Leadership Style (X) with the dependent variable, namely the loyalty of village officials (Y) which is quite strong. The coefficient of determination (????2) is 0.260%, this figure indicates that the contribution of the independent variable, namely the Village Head's Leadership Style (X) to the dependent variable (Y) is 26%, while the remaining 74% is influenced by other variables not included in this study. Testing the hypothesis shows that the t value is 2.216 > from the t table is 2.145. This proves the independent variable, namely the Village Head's Leadership Style, has a significant (significant) effect on the loyalty variable of village officials